A decision support system for the re-equilibrium of PPP contracts - Shalaby, Amira Mohamed (AUC Knowledge Fountain, 2015)
Public Private Partnership (PPP) contracts tend to have longer contract durations compared to other conventional procurement methods. Due to their prolonged nature, PPP contracts are extremely prone to contract renegotiation along their lifecycles in comparison to other forms of contracts with shorter durations. The common outcomes of the renegotiation process may include: increasing the service charges, increasing the concession period, or paying a lump sum amount to the party of concern in order to maintain a fixed rate of return and keep the return on equity constant. In this research, a framework is developed in order to calculate the renegotiation process outcomes and facilitate the decision making process of choosing the optimum scenario that preserves the rights and the interests of all the stakeholders. This is done using a weighted sum model to calculate the weights and ranks of a number of factors influencing the stakeholders' decisions. A Decision Support System (DSS) is developed with the aid of Microsoft Excel 2013, Visual Basic for Applications (VBA) programming language, and the Precision Tree 5.5 for Excel add-in. The data for the model is obtained from a case study of a wastewater treatment plant in Egypt. The results obtained from the model are close to the ones obtained from the Independent Financial Expert (IFE) of the wastewater treatment plant.